The effects of climate change on agriculture and food security - Ndruru, Juan Feron; Masjud, Yunita Ismail (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Climate change is an environmental issue that affects a lot of human activities and causes damages to the Earth which of course will have linkages to the living creatures’ life. Agriculture is a part of human activities that becomes a source of human life and influences food security. It also contributes to generating oxygen (O2) and absorbing carbon dioxide (CO2) in the air. As climate change is getting uncertain each time and influenced by some factors that make climate change getting worse, this gives some impacts on agriculture and food security. Besides, there will be other issues that come from agriculture and food security matters due to climate change, such as hunger due to food crisis, etc. Thereupon, we need to know the effects of climate change on agriculture and food security to mitigate and adapt to climate change. The objective of this literature study is to elucidate the impacts of climate change on agriculture and food security to understand the things that should be done to tackle the possibilities of bad impacts on human life. Methods: The method that was implemented was a qualitative method that utilized literature review to do the identification, evaluation and collecting information that was needed. Some papers and journals related to climate change, agriculture, and food security were used in literature review. Findings: Food production from crops and livestock is crucial for global food security. However, significant challenges to food production arise due to climate change and related factors. Heat exposure significantly affects livestock performance and welfare. Climate change also leads to soil erosion, resulting in decreased soil productivity, loss of carbon and organic nutrients, and reduced soil fertility. Conclusion: It is suggested to comprehend the effects of climate change on agriculture that will influence food security along with the well-being of people in running life.